2005
DOI: 10.1007/s00134-005-2706-1
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial viral ventilator-associated pneumonia in the intensive care unit: a prospective cohort study

Abstract: We found a high incidence of HSV-1 infection in VAP patients; however, nosocomial viral VAP is likely to be rare in ICU, as assessed by the absence of respiratory virus-induced VAP identified in this prospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 33 publications
4
49
1
Order By: Relevance
“…Furthermore, HSV-2 was not detected in any of the patients. In comparison to previous reports that estimated lower prevalence of HHVs at the intensive care unit (ICU) (less than 5%) (37)(38)(39), there was a notably greater prevalence of HHVs at the PICU in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, HSV-2 was not detected in any of the patients. In comparison to previous reports that estimated lower prevalence of HHVs at the intensive care unit (ICU) (less than 5%) (37)(38)(39), there was a notably greater prevalence of HHVs at the PICU in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Third, nonbacterial causes of pneumonia. It has been seen recently that herpes simplex virus and cytomegalovirus could be the potential causes of VAP (38)(39)(40)(41). We did not search for viruses in our samples.…”
Section: Discussionmentioning
confidence: 57%
“…However, data on viral nosocomial pneumonia are scarce, and the role of respiratory viruses as a cause of nosocomial pneumonia is probably limited. Daubin et al [36], in a prospective study on 139 mechanically ventilated patients, showed that only two out of 39 patients suspected of having developed VAP had a respiratory sample (tracheal aspirate) positive for respiratory viruses (one enterovirus and one influenza). Notably, in this study, 12 patients (31%) had a sample positive for HSV and one for cytomegalovirus [36].…”
Section: Respiratory Virusesmentioning
confidence: 99%